Multiple myometrial cysts micmicking multiple fibroid uterus - Ramesh, B.; Ghanti, Rachana; Devadiga, Veena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Adenomyosis is the presence of endometrial glands and stroma in the context of the myometrium, with adjacent smooth muscle hyperplasia. It may be diffuse or cystic. Adenomyotic cysts of the uterus are extremely rare. A 31 years old nulligravida woman presented to our OPD with complaints of severe dysmenorrhea and back pain since 8 months. Transvaginal ultrasound revealed retroverted uterus with diffuse adenomyosis with intramyometrial endometriotic cysts in both cornual areas, both adnexa showing multiple small endometriotic cysts. On Laparoscopy – cystic masses around 5x4cm was found near the cornua and anterior uterine wall, which were excised and diagnosed as adenomyotic cyst on histopathology.